The Stages of Pedagogical Science Development: Comparison in Kazakhstan and China (Journal of Educational Sciences, 2017)
Research in the area of comparative education in the era of globalization allows to understand better the characteristics of historical development, to capture current trends and make recommendations. The article aims to compare the development of pedagogical science in Kazakhstan and China, two neighboring countries, construct periodisations for each country, and develop recommendations. The periodization of development in pedagogical science in Kazakhstan by authors G. M. Khrapchenkov, A. N. Ilyasova, A. K. Kusainova,K. B. Zharikbaev and S. Kaliyeva are studied. The research of China periodization by authors GU Mingyuan, Wang Daizong and Vanjani, Li Singo are studied. The options of the authors’ periodisations are proposed for discussions of conditional comparison stages. The initial period of pedagogical science development in XX century for Kazakhstan and China is characterised by a tendency to study foreign advanced ideas of education development, appear adapted interpretations and thoughts of the world scientists-teachers. The second half of the twentieth century is strongly influenced by the Soviet pedagogical thoughts on the basis of ideology and the philosophy of dialectical materialism. At thesame time local scientists develop local pedagogical schools. In the late twentieth century an active establishment and development of new scientific and educational schools is detected. In the XXI century the internationalization of education and science of Kazakhstan and China is observed.
Keywords: pedagogical science; Kazakhstan; China; periodization; scientific school